Strategi Layanan Bimbingan Konseling Terhadap Siswa Sekolah Dasar Dalam Mengembangkan Konsep Diri Pada Masa Pandemi Covid-19 : Literatur Review - Fajrin, Gardina Aulia; Wahyuni, Sri; Muhid, Abdul (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
Education is very important in supporting the knowledge and potential of students, therefore having a positive self-concept makes students more optimistic. Therefore, this study aims to review the strategy of counseling guidance services for elementary school students in developing self-concept during the covid-19 pandemic. This research method is a literature review where the researcher collects various previous sources. The data analysis technique used content analysis. The theoretical basis in this study explains the self-concept, the role and components of comprehensive guidance and counseling services, as well as the strategy of guidance and counseling services in developing self-concept in elementary school children. The strategy includes four components, namely, basic services, responsive services, individual planning, system support. The role of parents and teachers is important in developing self-concept. In addition, the online counseling system (cyber counseling) can develop self-concept in students through application media.